A Cross-national Analysis of Gender Equality and the Shift from Collegiality to Managerialism in Higher Education Policy - Bagilhole, Barbara (Acta Paedagogica Vilnensia, 2012)
This paper reports on part of a comparative eight-country study of higher education (HE) policy across Australia, Ireland, New Zealand, South Africa, Sweden, Turkey, and UK. It explores the uneven shift from the traditional collegial to a new managerialist organisational form both between different countries and even within the countries. It provides an overview of each country’s HE system and then analyses the gendered character of academic leadership. Finally, it comes to the conclusion that there is no indication that either the collegial or the managerial system is more conducive to gender equality. It is clear that the strength or absence of Equal Opportunity and Affirmative Action frameworks has a greater impact on gender equality in universities.
Keywords: higher education policy; collegiality; managerialism; gender equality